2022
DOI: 10.1177/20533691221136309
|View full text |Cite
|
Sign up to set email alerts
|

The effect of cognitive-behavioral therapy on stress and anxiety of women with premature ovarian insufficiency: A randomized controlled trial

Abstract: The aim of this study was to determine the effect of cognitive-behavioral therapy (CBT) on stress and anxiety (primary outcomes) and self-esteem and depression (secondary outcomes) in women with premature ovarian insufficiency (POI). This randomized controlled trial was performed on 50 women known with POI in Tabriz, Iran, in 2021. Participants were randomly assigned to CBT and control groups. CBT was provided in eight sessions of 45–60 min once a week with five to seven people. The Spielberger State-Trait Anx… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 48 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…The meetings were provided in eight sessions of 45–60 min once a week. Using PSS, they concluded that CBT can contribute to a reduction in stress [ 23 ]. The results of both studies are in line with the present one.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The meetings were provided in eight sessions of 45–60 min once a week. Using PSS, they concluded that CBT can contribute to a reduction in stress [ 23 ]. The results of both studies are in line with the present one.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion criteria: mothers were required to have a daughter aged 8–9 with precocious puberty symptoms [ 22 ], a minimum of secondary school literacy, having a smart phone, having stress and anxiety due to their daughters’ precocious puberty, and a score of 35–65 (moderate and relatively severe) on STAI (State-Trait Anxiety Inventory) and above 21.8 on PSS (Perceived Stress Scale) [ 23 ]. Exclusion criteria: having a history of mental disorders according to the person’s statement, experiencing a severe mental health crisis in the last three months, such as the death of a relative, taking neuropsychiatric medications, other physical or mental problems, and participating in similar studies.…”
Section: Methodsmentioning
confidence: 99%